Kejawen dalam Pandangan Islam - Ali Imron; Anggi Eryana; Rohmat Suprapto (Edudeena: Journal of Islamic Religious Education, 2023)
Abstract: The aim of this research is to find out the activities of Javanese culture which is known as kejawen in the village of Demak. People who embrace Islam but do not refuse to preserve the culture of their ancestors. The research methodology used is qualitative by direct observation and interviews with competent informants and documentation. The results of this study were obtained that, starting from the meaning of kejawen in the literal sense, it means Javanese belief. Furthermore, this term refers to everything related to beliefs and customs that develop in Javanese society in particular. From a philosophical point of view, kejawen presents certain teachings whose purpose is to lead people to have good manners, noble values, and an existing divine perspective. With the inclusion of various religious sects in Javanese society over a long period of time, the Kejawen belief experienced acculturation with various other religions. Kejawen Islamic culture is still thick with things that contain shirk, which in Islam itself strictly prohibits this which is explained in the Koran and hadith.